Синтез поликристаллических алмазов с применением сплавов-катализаторов системы Ni–Cr–X (Mo, Ti, Ta) - Ножкина, А.В.; Лаптев, А.И.; Ермолаев, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Influence of mechanical properties of alloys-catalysts on mechanical properties of synthetic
polycrystalline composite diamond materials is studied. It is established, that increase of durability
of an alloy-catalyst leads to increase of durability of a metal sheaf and durability of a diamond
composite material. The established dependence is observed at preservation of plasticity of a sheaf